Using Sketches to Communicate Interaction Protocols of an Indigenous Community, In : Proceedings of the 14th Participatory Design Conference: Short Papers, Interactive Exhibitions, Workshops - Tariq, Zaman; Heike, Winschiers-Theophilus; Franklin, George; Yeo, Alvin Wee; Hasnain, Falak; Naska, Goagoses (ACM New York, NY, USA, 2016)
Being engaged in long term collaborations with indigenous communities requires a continuous adjustment of interaction protocols beyond set projects. Although the Long Lamai community in Malaysia developed a detailed cultural protocol for guest researchers, numerous conflicts were still recorded. In this paper we present our most recent approach to overcome the cross-cultural communication gaps using sketches, as developed by the local community members. We present a validation session that took place between the community members and guest researchers. We confirm the success of the sketch session, as guest researchers followed the underlying themes of the interaction protocols and internalised the concepts.